1998
DOI: 10.1161/01.cir.98.17.1802
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers in Interventional Cardiology

Abstract: I n more than 20 years since the first percutaneous coronary revascularization procedures, the field of interventional cardiology has proliferated beyond all expectations. Now more than 1 million procedures are performed worldwide each year. Stenting has revolutionized the field, which previously relied on balloon dilatation in the majority of patients. With Ϸ50% of patients now undergoing stent implantation, the groundwork is laid for further important advances. In this article, we discuss the 4 most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
116
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(117 citation statements)
references
References 184 publications
0
116
0
1
Order By: Relevance
“…Fitzgibbon et al (3) found that patency rates of saphenous vein grafts in patients undergoing CABG 1, 5, and 10 years after surgery were 78%, 65, and 57%, respectively. Although statins improve graft patency by ϳ24 -29% (4), poor long term patency, and the lack of other pharmacologic agents preventing graft failure, necessitates the search for effective alternative therapies and surgical techniques (5). The cellular processes underlying intimal hyperplasia and vein graft failure are smooth muscle cell (SMC) proliferation and migration.…”
mentioning
confidence: 99%
“…Fitzgibbon et al (3) found that patency rates of saphenous vein grafts in patients undergoing CABG 1, 5, and 10 years after surgery were 78%, 65, and 57%, respectively. Although statins improve graft patency by ϳ24 -29% (4), poor long term patency, and the lack of other pharmacologic agents preventing graft failure, necessitates the search for effective alternative therapies and surgical techniques (5). The cellular processes underlying intimal hyperplasia and vein graft failure are smooth muscle cell (SMC) proliferation and migration.…”
mentioning
confidence: 99%
“…Coronary stenting prevents acute elastic recoil and negative remodelling, but does not have any effect against neointimal formation (5). In fact, stenting appears to actually increase cell proliferative components of intimal hyperplasia in restenosis (6)(7)(8)(9). Although multiple cell types, cytokines and mediators all play roles in the complex process of neointimal formation, there is a final common pathway: the entry of VSMCs into the cell cycle.…”
Section: Mechanisms Of Restenosismentioning
confidence: 99%
“…[17][18] Recent clinical trials of polymerand non-polymer-based paclitaxel-and sirolimus-eluting stents have demonstrated promising results in the treatment of de novo coronary lesions. 19 -24 Because early studies investigating the biocompatibility of synthetic polymers showed significant inflammatory and proliferative responses, [25][26] the use of nonpolymer-based local drug delivery became an attractive approach.…”
Section: See P 1906mentioning
confidence: 99%